The Renewed Promise of Medical Informatics - van Bemmel, J. H.; McCray, A. T. (Yearbook of Medical Informatics, 2016)
The promise of the field of Medical Informatics has been great and its impact has been significant. In 1999, the Yearbook editors of the International Medical Informatics Association (IMIA) - also the authors of the present paper - sought to assess this impact by selecting a number of seminal papers in the field, and asking experts to comment on these articles. In particular, it was requested whether and how the expectations, represented by these papers, had been fulfilled since their publication several decades earlier. Each expert was also invited to comment on what might be expected in the future. In the present paper, these areas are briefly reviewed again. Where did these early papers have an impact and where were they not as successful as originally expected? It should be noted that the extraordinary developments in computer technology observed in the last two decades could not have been foreseen by these early researchers. In closing, some of the possibilities and limitations of research in medical informatics are outlined in the context of a framework that considers six levels of computer applications in medicine and health care. For each level, some predictions are made for the future, concluded with thoughts on fruitful areas for ongoing research in the field.
Keywords: Medical Informatics; history; forecasting; computing methodologies; information systems; electronic health records; clinical decision support